Clinical advances of hypoxia-activated prodrugs in combination with radiotherapy - Mistry, I; Thomas, M; Calder, E; Conway, S; Hammond, E (Elsevier, 2017)
With the increasing incidence of cancer worldwide, the need for specific, effective therapies is ever more urgent. One example of targeted cancer therapeutics is hypoxia-activated prodrugs (HAPs), also known as bioreductive prodrugs. These prodrugs are inactive in cells with normal oxygen levels but in hypoxic cells (with low oxygen levels) undergo chemical reduction to the active compound. Hypoxia is a common feature of solid tumors and is associated with a more aggressive phenotype and resistance to all modes of therapy. Therefore, the combination of radiotherapy and bioreductive drugs presents an attractive opportunity for synergistic effects, as the HAP targets the radiation resistant hypoxic cells. HAPs have typically been precursors of DNA damaging agents, but a new generation of molecularly targeted HAPs is emerging. By targeting proteins associated with tumorigenesis and survival, these compounds may result in greater selectivity over healthy tissue. We review the clinical progress of HAPs as adjuncts to radiotherapy, and conclude that the use of HAPs alongside radiation is vastly underexplored at the clinical level.